DETERMINE THE STRAIN - STRESS STATE OF OVERPASS WITH INCLUDING SPATIAL WORK - Medvedev, K. V.; Malgin, M. H. (Science and Transport Progress, 2010)
In the article the analysis of design models used for the determination of efforts for elements of an automobile bridge trestle is carried out. The curvilinear rod, linear rod, and volume models are considered as design ones. Cases of spatial work of the structure are considered at different variants of loading.